Pelaksanaan Supervisi Kinerja Guru di Sekolah Dasar Negeri 88 Palembang - Ibrahim; Annur, Saipul; Rahma, Iya (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
This research is titled "Implementation of Teacher Performance Supervision at SD Negeri 88 Palembang." This study aims to understand how the implementation of teacher performance supervision is carried out at SD Negeri 88 Palembang. The research design employed in this study is field research with a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and conclusion. The findings of the research indicate that the implementation of teacher performance supervision has been carried out effectively and regularly every year. The stages of teacher performance supervision consist of planning, implementation, and evaluation. The program for teacher performance supervision has been executed according to the established plan, and the process has been well-implemented. This is evident in the procedural execution of teacher performance supervision, covering the planning, implementation, and evaluation stages. In the planning stage, the school head forms a supervision team and reviews records or documents related to the subject of supervision. The implementation stage involves using the classroom visitation technique, where the school head actively participates in the field. Finally, the evaluation stage assesses the results of the well-executed supervision, with the school head, supervision team, and subject of supervision collectively discussing the outcomes. Challenges in the implementation of supervision include the duration or timing of supervision. School heads may sometimes have limited time to conduct supervision, and teachers may not always be prepared for the routine supervisory process, viewing it as a daunting activity because their superiors are the ones evaluating them. Solutions to these challenges include effective time management by school heads and changing the mindset of teachers to see supervision not as a threatening activity but as an evaluation tool to improve their performance.